APLIKASI PREBIOTIK PADA PAKAN KOMERSIAL UNTUK MENINGKATKAN KINERJA PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - Afrita Jayati Sudiarto; Mustahal Mustahal; Achmad Noerkhaerin Putra (Jurnal Perikanan dan Kelautan, 2014)
This research aimed to evaluate the effect of prebiotic to promote the growth of tilapia. Fish were fed four times daily in ad satiation. The Feed used were commercial feed pellet dry with 32% carbohydrates, 7% lipids and 30% proteins. The prebiotic used was extracted from sweet potato varieties sukuh. The experiment were done with three treatments and 3 replicates, namely control A (0% prebiotic), B (1% prebiotic) and C (2% prebiotic). The results showed that application of prebiotic in feed can promote better tilapia growth compared to control. The treatment with the addition of 1% prebiotics showed the best result on promoting tilapia growth, feed efficiency, bacteria population in gastrointestinal tract, apparent digestibility and nutrition retention among other treatments respectively.Keyword: prebiotic, growth performance, tilapia (Oreochromis niloticus).